Exosomes and Metabolic Function in Mice Exposed to Alternating Dark-Light Cycles Mimicking Night Shift Work Schedules - Khalyfa, Abdelnaby; Poroyko, Valeriy A.; Qiao, Zhuanhong; Gileles-Hillel, Alex; Khalyfa, Ahamed A.; Akbarpour, Mahzad; Almendros, Isaac; Farré, Ramon; Gozal, David (Frontiers in Physiology, 2017)
Sleep is an important modulator of metabolic function. Disruptions of sleep in circadian rhythm are common in modern societies and are associated with increased risk of developing cardiometabolic disorders. Exosomes are ubiquitous extracellular vesicles that may play a mechanistic role in metabolic derangements. We hypothesized that alternating dark-light cycles mimicking shift work in mice would alter fecal microbiota and colonic epithelium permeability and alter plasma exosome cargo and metabolic function. C57BL/6 mice were randomly assigned to (i) control day light (CL), or (ii) inverted dark-light every 2 weeks for 8 weeks (IN). Body weight, fat mass and HOMA-IR were measured, along with Tregs, metabolic and resident macrophages in visceral white adipose tissue (vWAT). Fecal water samples were incubated with confluent colonic epithelium cell cultures in electric cell-substrate impedance sensing (ECIS) arrays, and plasma exosomes were added to differentiated adipocytes and insulin-induced pAKT/AKT expression changes were assessed by western blots. Mice exposed to IN showed elevated HOMA-IR, and their fecal samples showed altered microbiota which promote increased permeability of the colonic epithelial cell barrier. Plasma exosomes decreased pAKT/AKT responses to exogenous insulin compared to CL, and altered expression of circadian clock genes. Inflammatory macrophages (Ly-6chigh) were increased in IN-exposed vWAT, while Tregs were decreased. Thus, gut microbiota and the cargo of plasma exosomes are altered by periodic shifts in environmental lighting, and effectively alter metabolic function, possibly via induction of systemic inflammation and altered clock expression in target tissues. Further exploration of exosomal miRNA signatures in shift workers and their putative metabolic organ cell targets appears warranted.